ANALYSIS OF INDONESIAN LANGUAGE ERRORS IN LINGUISTIC CATEGORIES IN OBSERVATION REPORT TEXTS OF GRADE VIII STUDENTS - Naila Riski Ahsani; Salsabilah, Shifa Harun; Fauziah, Ulfah; Nurjamilah, Ai Siti (Media Inovasi Pendidikan dan Publikasi, 2024)
This study aims to analyze language errors in students’ observation report texts. The analysis covers phonology, morphology, syntax, and semantics to understand the types and causes of common errors. The research method employed is descriptive analysis with a qualitative approach applied to data collected from several student observation reports. The results indicate that the most dominant errors occur in phonology, particularly in incorrect vowel pronunciation, omission of final consonants, and substitution of certain sounds. These findings are expected to serve as an evaluation tool to improve language learning and accurate pronunciation in students' observation text writing.